La pensée sur les deux infinis - Kaplan, Francis (Revue des sciences philosophiques et théologiques, 2009)
The author shows that, according to Pascal, understanding a pensée correctly depends on being able to classify it, and that if we accept Lafuma’s classification, none of the justifications given for the place of the so-called pensée of the two infinities is acceptable. And this pensée, one of the Apology’s most important, would thus be incomprehensible, along with many others. Given that Lafuma’s classification is founded on nothing more than hypotheses, and since another is made possible by Pascal’s manuscript indications, which are incontestable facts, it is to the latter classification that we must refer. Indeed, doing so brings out the meaning of this pensée.